Inhibitory to non-inhibitory evolution of the ζ subunit of the F1FO-ATPase of Paracoccus denitrificans and α-proteobacteria as related to mitochondrial endosymbiosis - Mendoza-Hoffmann, Francisco; Yang, Lingyun; Buratto, Damiano; Brito-Sánchez, Jorge; Garduño-Javier, Gilberto; Salinas-López, Emiliano; Uribe-Álvarez, Cristina; Ortega, Raquel; Sotelo-Serrano, Oliver; Cevallos, Miguel Ángel; Ramírez-Silva, Leticia; Uribe-Carvajal, Salvador; et al. (Frontiers in Molecular Biosciences, 2023)
Introduction: The ζ subunit is a potent inhibitor of the F1FO-ATPase of Paracoccus denitrificans (PdF1FO-ATPase) and related α-proteobacteria different from the other two canonical inhibitors of bacterial (ε) and mitochondrial (IF1) F1FO-ATPases. ζ mimics mitochondrial IF1 in its inhibitory N-terminus, blocking the PdF1FO-ATPase activity as a unidirectional pawl-ratchet and allowing the PdF1FO-ATP synthase turnover. ζ is essential for the respiratory growth of P. denitrificans, as we showed by a Δζ knockout. Given the vital role of ζ in the physiology of P. denitrificans, here, we assessed the evolution of ζ across the α-proteobacteria class. Methods: Through bioinformatic, biochemical, molecular biology, functional, and structural analyses of several ζ subunits, we confirmed the conservation of the inhibitory N-terminus of ζ and its divergence toward its C-terminus. We reconstituted homologously or heterologously the recombinant ζ subunits from several α-proteobacteria into the respective F-ATPases, including free-living photosynthetic, facultative symbiont, and intracellular facultative or obligate parasitic α-proteobacteria. Results and discussion: The results show that ζ evolved, preserving its inhibitory function in free-living α-proteobacteria exposed to broad environmental changes that could compromise the cellular ATP pools. However, the ζ inhibitory function was diminished or lost in some symbiotic α-proteobacteria where ζ is non-essential given the possible exchange of nutrients and ATP from hosts. Accordingly, the ζ gene is absent in some strictly parasitic pathogenic Rickettsiales, which may obtain ATP from the parasitized hosts. We also resolved the NMR structure of the ζ subunit of Sinorhizobium meliloti (Sm-ζ) and compared it with its structure modeled in AlphaFold. We found a transition from a compact ordered non-inhibitory conformation into an extended α-helical inhibitory N-terminus conformation, thus explaining why the Sm-ζ cannot exert homologous inhibition. However, it is still able to inhibit the PdF1FO-ATPase heterologously. Together with the loss of the inhibitory function of α-proteobacterial ε, the data confirm that the primary inhibitory function of the α-proteobacterial F1FO-ATPase was transferred from ε to ζ and that ζ, ε, and IF1 evolved by convergent evolution. Some key evolutionary implications on the endosymbiotic origin of mitochondria, as most likely derived from α-proteobacteria, are also discussed.